The Impact of Implementing Artificial Intelligence Strategies on Institutional Excellence: A Study on Administrative Staff in Public Schools in the City of Jeddah - Al-Otaibi, Huda (The Arab Journal of Administration, 2025)
The current study aims to identify the impact of implementing artificial intelligence strategies on institutional excellence among administrators in public schools in Jeddah. This was achieved by determining the level of implementation of artificial intelligence strategies in public schools in Jeddah, examining the reality of institutional excellence, and determining the relationship between the implementation of artificial intelligence strategies and their role in institutional excellence in public schools in Jeddah. The study followed a descriptive correlational approach. The current study relied on a simple random sampling method to select the research sample, with a sample size of (211) administrators representing the study population. A questionnaire was also used as a study tool to identify the impact of implementing artificial intelligence strategies on institutional excellence in public schools in Jeddah.The study reached a set of results indicating that the level of implementation of artificial intelligence strategies in public schools in Jeddah was extremely high. The results also showed an important level of institutional excellence in these schools, with a strong and statistically significant positive effect of implementing artificial intelligence strategies in their three dimensions on institutional excellence. All dimensions demonstrated a strong positive impact that contributed to significantly improving performance quality and developing educational and administrative processes.